Reading Non-Literary Text Distance Learning at Junior High School Level - Dyah Ayu Putri Utami; Teguh Setiawan Setiawan (Jurnal Pendidikan Indonesia, 2021)
This study aimed to describe the design, tools, methods, media, teaching materials, and assessments of reading non-literary text distance learning at junior high school level. The design of this study is qualitative descriptive. The sources of data in this study are Indonesian language teachers, junior high school students, and learning documents. The data in this study are documents of distance learning planning and implementation. The data collection techniques used were observations, interviews, and documentations. Some of the results of this study are: reading non-literary text distance learning was designed in combination and offline form; teacher have made a complete reading non-literary text distance learning lesson plan; the distance learning method used consists of lectures, discussions, and recitations. Permanent teaching materials used in this study were the Indonesian language textbooks for grade VII and VIII published by the Ministry of Education and Culture; the assessment used in reading non-literary text distance learning was a test conducted by using the Google Forms media. Based on the results of the study, PJJ is implemented in a varied way both in terms of planning, implementation and evaluation. All elements of PJJ implementation must improve the quality of PJJ itself. In addition, the use of online and offline learning designs by teachers must be balanced. This interactive, interesting, and innovative learning can successfully happen if all parties work together optimally.